Tes Diagnostik Four-tier untuk Menilai Miskonsepsi Siswa tentang Fluida: Sebuah Kisah dari Pengembangan hingga Pengukuran dari Tiga Lokasi Lingkungan - Erniwati Erniwati; Muhamad Arif Mahdiannur; Hunaidah Hunaidah (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop a Four-Tier Fluid Material Misconception Diagnostic Test instrument that can provide an overview of the misconception profile of high school students in Southeast Sulawesi. This study uses the Research and Development (R&D) method with XI grade high school students in three districts/cities in Southeast Sulawesi. The stages of the research adapting the Brog and Gall method are preliminary studies; product planning and design; and product testing. Data analysis techniques on content validity testing using V' Aiken; empirical validity testing using the Rasch approach with WINSTEP 3.73 software, the profile of misconceptions at the limited trial stage and broad trials using the categorization of the Diagnostic Four-Tier Test. From the results of the content validity test and empirical validity, it is shown that the diagnostic test instrument for the Four-Tier Misconception Test for Fluid Materials is in the valid and reliable category (r = 0.87 = 0.05). This research has succeeded in developing a diagnostic test instrument for the Misconception Four-Tier Test for Fluid Materials as many as 20 items which can describe the misconception profile of class XI high school students with good criteria. The highest misconception is in the Archimedes Law Sub-concept of 36.30%. Students' misconceptions on fluid material from research subjects were obtained by Kendari City by 29.50%; East Kolaka Regency by 35.70%; and Kabupaten Bombana by 32.20%.